DEVELOPING MACROMEDIA FLASH FOR TEACHING SPEAKING MATERIALS FOR STUDENTS - Ayu Trisna; Riyah Shibha Nasution (AICLL: ANNUAL INTERNATIONAL CONFERENCE ON LANGUAGE AND LITERATURE, 2018)
The aim of this study is to develop macromedia flash as a learning media for teaching speaking materials for students. Research and Development is used as the research method. Research Procedures are modified into four steps, they are: evaluation and need analysis, media design, validation and revision, and final production. The product has validated by expert validation. The expert is an English lecturer of English literature Department, State University of Medan which approved by Faculty of Languages and Arts. The instrument for collecting data is by using questionnaire. The data are analyzed by descriptive technique. The result shows that macromedia flash is advisability to use with the total assessment by expert validations is 91 (Good). With the result that macromedia flash is good and eligible to use for teaching speaking for students.